2022
DOI: 10.1200/jco.2022.40.16_suppl.8067
|View full text |Cite
|
Sign up to set email alerts
|

COVID vaccine immune response in patients with plasma cell dyscrasia: A systematic review.

Abstract: 8067 Background: The defective immune system in plasma cell dyscrasia places patients at a higher risk of developing a severe infection, which is one of the leading causes of death in such patients. In an era of a global pandemic, it is essential to protect them against COVID-19, but fewer effective plasma cells lead to a suboptimal response to vaccines. There is still a lack of evidence whether the seroconversion is truly clinically relevant and if patients with plasma cell disorders would benefit from frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Dear Editor, We would like to share ideas on the publication 'COVID-19 vaccine immune response in patients with plasma cell dyscrasia: a systematic review'. 1 The purpose of this systematic review was to assess the immunological response to COVID-19 vaccinations in plasma cell dyscrasia patients and provide insights to improve clinical management. The review adhered to PRISMA principles and included nine papers (seven prospective and two retrospective studies) among 59 found via internet database searches.…”
Section: Therapeutic Advances In Vaccines and Immunotherapymentioning
confidence: 99%
“…Dear Editor, We would like to share ideas on the publication 'COVID-19 vaccine immune response in patients with plasma cell dyscrasia: a systematic review'. 1 The purpose of this systematic review was to assess the immunological response to COVID-19 vaccinations in plasma cell dyscrasia patients and provide insights to improve clinical management. The review adhered to PRISMA principles and included nine papers (seven prospective and two retrospective studies) among 59 found via internet database searches.…”
Section: Therapeutic Advances In Vaccines and Immunotherapymentioning
confidence: 99%